2016
DOI: 10.1002/adhm.201600913
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Microgel Based Modular Bioinks for Uncoupled Cellular Micro‐ and Macroenvironments

Abstract: Modular bioinks based on single cell microgels within distinct injectable prepolymers enable uncoupling of biomaterials' micro- and macroenvironments. These inks allow biofabrication of 3D constructs that recapitulate the multiscale modular design of native tissues with a single cell resolution. This approach represents a major step forward in endowing engineered constructs with the multifunctionality that underlies the behavior of native tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 49 publications
1
104
0
Order By: Relevance
“…Numerous studies have demonstrated the generation of cell-laden hydrogel microparticles using microfluidic devices[64]. Recent innovations even allowed for microfluidic encapsulation of individual cells in microgels that are only marginally larger than the cell they contain [66]. Spatial placement of the cell in these microgels is of high importance to prevent cell egression; it has been reported that delayed on-chip gelation places cells in the microgel’s center, which enables long-term culture [67].…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the generation of cell-laden hydrogel microparticles using microfluidic devices[64]. Recent innovations even allowed for microfluidic encapsulation of individual cells in microgels that are only marginally larger than the cell they contain [66]. Spatial placement of the cell in these microgels is of high importance to prevent cell egression; it has been reported that delayed on-chip gelation places cells in the microgel’s center, which enables long-term culture [67].…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%
“…As discussed in previous sections, the engineering strategies to gain spatiotemporal control over biomaterials through sophisticated chemistries and fabrication techniques are expected to pave the way for the realization of such biomimetic systems. The concept of bottom-up tissue engineering offers a promising pathway to generate multiscale structures via assembling heterogeneous synthons, such as proteins, nucleic acids, cells, nanoparticles, and other bioactive components within the cell-laden hydrogel matrices [66, 78, 323325]. …”
Section: Future Perspectivesmentioning
confidence: 99%
“…A number of advanced strategies has been developed to enable the in situ presentation of a crosslinker upon a chemical or physical trigger, such as changing pH, irradiation, and temperature. 6,[18][19][20][21] However, the commonly used acid-, photo-, and heat-triggered crosslinking strategies are detrimental to cell survival and function, or are technically challenging as they require the formation of labile crosslinker-laden complexes. 13,22,23 Alternatively, gelation of emulsified hydrogel precursor droplets can be induced via the diffusionbased supplementation of crosslinker molecules, which does not depend on technically challenging or cytotoxic triggers.…”
Section: Introductionmentioning
confidence: 99%
“…Although tissue engineers have recently started to integrate these complex functions into smart (i.e. instructive and responsive) biomaterials, [47][48][49][50][51][52][53][54][55][56][57][58] their use has remained limited to bulk constructs that do not recapitulate the modular design of native tissues. The modular tissue engineering toolbox is thus currently lacking in situ biochemically and biomechanically tunable building blocks, which are essential to incorporate both the dynamicity and multiscale modularity of native tissue into artificial tissue constructs.…”
Section: In Situ Tunable Building Blocksmentioning
confidence: 99%
“…As such, IAMF enabled one-step rapid manufacturing of 3D modular cell-laden biomaterials with distinct cellular micro-and macroenvironments, which is a promising, yet challenging direction in the field of tissue engineering. [49,51,52] The same onestep injection molding approach was leveraged to produce a multiscale modular tissue construct with optimized cellular micro-and macroenvironments. The construct consisted of insulin producing pancreatic beta cells (MIN6, beige with blue nuclei) that were encapsulated in alginate microparticles (green).…”
Section: Iamf Enables One-step Manufacturing Of 3d Multiscale Modularmentioning
confidence: 99%